Sectoral trade globalization - Crespo, N.; Palan, N.; Simões, N. (Handbook of research on the empirical aspects of strategic trade negotiations and management, 2021)
This chapter aims to shed light on the trends of sectoral trade globalization. This component of trade globalization is often neglected. An accurate evaluation of sectoral trade requires the analysis of the interdependencies of countries and the consideration of distance as a central dimension of trade globalization. As such, sectoral trade globalization is one aspect of a more complex and multi-dimensional phenomenon. Data show that sectoral trade globalization has increased significantly over the last 50 years irrespective of the characteristics of individual sectors. One relevant insight is that the level of trade globalization is on average still different for high-tech sectors compared to low-tech and medium-low-tech sectors even though the former could increase their bilateral trade relationships over time. Even though protectionist tendencies as well as the COVID-19 pandemic have led to a vivid discussion about the return to more local or regional production schemes, digitalization processes could still have the potential to further integrate countries' trade networks.